Peran Bagian Protokol Sekretariat Daerah Kota Palembang dalam Menunjang Kinerja Sekretariat Daerah Kota Palembang - Yugo Panji Alam; Ignasius Hendrasmo; Muhammad Abduh (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
The Role of the Protocol Section of the Palembang City Regional Secretariat in Supporting the Performance of the Palembang City Regional Secretariat. The research method used is to use qualitative research methods with observational data collection techniques, interviews and documentation. The results showed that the Role of the Protocol Section of the Palembang City Regional Secretariat in Supporting the Performance of the Palembang City Regional Secretariat. The role of this protocol is very decisive in assisting the Palembang city regional office in completing its work, but the protocol in carrying out its duties and functions is based on existing policies. The Palembang City Setda Protocol must be able to do its job well, one of its strategies is to coordinate and communicate optimally with various related parties, then carry out innovations and changes in accordance with the actual conditions of the times, the goal is that every activity that exists of the Palembang City Setda can run optimally and better. The Palembang City Setda Protocol must have good communication skills, because the role of the Protocol itself is as a liaison between agencies, private institutions or the community with the Palembang City Setda, both meeting issues and activities or events to be carried out. Mistakes and misconduct in work and in the implementation of activities in the Palembang City Setda occur, but with the experience and words of Setda employees, of course, the problems can be overcome and corrected properly.